2009
DOI: 10.1021/bi901112q
|View full text |Cite
|
Sign up to set email alerts
|

The Major Surface Carbohydrates of the Echinococcus granulosus Cyst: Mucin-Type O-Glycans Decorated by Novel Galactose-Based Structures

Abstract: The cestodes constitute important but understudied human and veterinary parasites. Their surfaces are rich in carbohydrates, on which very little structural information is available. The tissue-dwelling larva (hydatid cyst) of the cestode Echinococcus granulosus is outwardly protected by a massive layer of carbohydrate-rich extracellular matrix, termed the laminated layer. The monosaccharide composition of this layer suggests that its major carbohydrate components are exclusively mucin-type O-glycans. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 49 publications
1
20
0
1
Order By: Relevance
“…In TLC test, the strip of the LL Ag bands may indicate the presence of a wide range of different sugar in this layer, while PS Ag and CF Ag showed 2 bands or no band, respectively. In agreement with this result it has been shown that laminated layer is highly glycosylated ( 38 - 40 ).…”
Section: Discussionsupporting
confidence: 85%
“…In TLC test, the strip of the LL Ag bands may indicate the presence of a wide range of different sugar in this layer, while PS Ag and CF Ag showed 2 bands or no band, respectively. In agreement with this result it has been shown that laminated layer is highly glycosylated ( 38 - 40 ).…”
Section: Discussionsupporting
confidence: 85%
“…Finally, in agreement with intense mucin biosynthesis, a number of CW clusters encode enzymes and transporters involved in the assembly of O -glycans ( Table 7 ). In particular, probably reflecting the marked predominance of galactose in the major glycans purified from the laminated layer [116], several transcripts correspond to proteins participating in galactose metabolism, the synthesis of UDP-galactose and its translocation across Golgi membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Certain of these N-terminal extensions bear unpaired cysteine residues, coincident with evidence that disulfide bonds contribute to the LL structure (7). The LL mucin glycans are now largely defined (13, 14). …”
Section: Introductionmentioning
confidence: 99%